2022
DOI: 10.3390/pharmaceutics14061216
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Therapeutic Drug Monitoring of Tyrosine Kinase Inhibitors in Routine Clinical Practice: A Pilot Study

Abstract: Introduction: The main goal of treatment in cancer patients is to achieve the highest therapeutic effectiveness with the least iatrogenic toxicity. Tyrosine kinase inhibitors (TKIs) are anticancer oral agents, usually administered at fixed doses, which present high inter- and intra-individual variability due to their pharmacokinetic characteristics. Therapeutic drug monitoring (TDM) can be used to optimize the use of several types of medication. Objective: We evaluated the use of TDM of TKIs in routine clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Age-related inter-individual variability has already been demonstrated for many treatments, but not for all TKIs [ 47 , 48 ]. Data are only available for vemurafenib [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age-related inter-individual variability has already been demonstrated for many treatments, but not for all TKIs [ 47 , 48 ]. Data are only available for vemurafenib [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Yet, retrospective audits of TKIs in clinical practice have shown that achievement of targeted drug exposure correlates with treatment response with, for example, imatinib, nilotinib, dasatinib, erlotinib, sunitinib, and sorafenib. 41,42 The following table…”
Section: % 5fu Catabolized By Other Pathways Dose Reduction For Some ...mentioning
confidence: 99%
“…Furthermore, genetic testing cannot measure patient characteristics such as adherence to treatment, a known impact on clinical outcome, nor environmental factors (food–drug and drug–drug interactions, including pharmacodynamic and other non‐P450 drug interactions) 40 . Yet, retrospective audits of TKIs in clinical practice have shown that achievement of targeted drug exposure correlates with treatment response with, for example, imatinib, nilotinib, dasatinib, erlotinib, sunitinib, and sorafenib 41,42 . The following table summarizes such points (Table 3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TDM was typically considered advantageous for drugs with a large inter-individual variability in exposure with relatively low intra-individual variation, a significant exposure–efficacy relationship, a narrow therapeutic window, and the availability of a validated bioanalytical assay. It has been postulated recently that this could also represent a useful tool to individualize dosing and optimize treatment using drugs with a wide therapeutic window and high cost [ 22 ].…”
Section: Introductionmentioning
confidence: 99%